2021
DOI: 10.3390/ijms22179329
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ift74 Leads to Slow Photoreceptor Degeneration and Ciliogenesis Defects in Zebrafish

Abstract: Cilia are microtubule-based structures projecting from the cell surface that perform diverse biological functions. Ciliary defects can cause a wide range of genetic disorders known collectively as ciliopathies. Intraflagellar transport (IFT) proteins are essential for the assembly and maintenance of cilia by transporting proteins along the axoneme. Here, we report a lack of Ift74, a core IFT-B protein, leading to ciliogenesis defects in multiple organs during early zebrafish development. Unlike rapid photorece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, there are a few exceptions. In zebrafish mutants of an IFT-B component, IFT88 (also named oval), Traf3ip1 (also named elipsa), and a Kinesin II family protein Kif3a, the axoneme and the OS are totally absent in photoreceptors (Krock and Perkins, 2008;Omori et al, 2008;Sukumaran and Perkins, 2009;Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are a few exceptions. In zebrafish mutants of an IFT-B component, IFT88 (also named oval), Traf3ip1 (also named elipsa), and a Kinesin II family protein Kif3a, the axoneme and the OS are totally absent in photoreceptors (Krock and Perkins, 2008;Omori et al, 2008;Sukumaran and Perkins, 2009;Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few exceptions. In zebrafish mutants of an IFT-B component, IFT88 (also named oval ), Traf3ip1 (also named elipsa ), and a Kinesin II family protein Kif3a, the axoneme and the OS are totally absent in photoreceptors (Krock and Perkins, 2008; Omori et al, 2008; Sukumaran and Perkins, 2009; Zhu et al, 2021). Interestingly, in IFT88 ( oval ) and Traf3ip1 ( elipsa ) mutants, a single spot-like γ-tubulin or centrin signal is detected in the apical region of photoreceptors, similar to zebrafish mak mutants, suggesting that basal bodies are formed in both mutants (Omori et al, 2008; Sukumaran and Perkins, 2009; Tsujikawa and Malicki, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish mutants were generated using CRISPR/Cas9 method with the following target sequences: ccdc57: 5 0 -GGGAAGAGGTCAGTGAGCTT -3 0 , ofd1: 5 0 -TATCAGACCTTCAAGAGCCG-3 0 , tmem67:5 0 -GGCAAGTGTCAGTGTCCTGA-3 0 . Cilia mutants (MZkif3a, ift74, ift88, and uts2r3) and Tg (urp1: GAL4; UAS: Kaede) transgenic lines were the same as previously reported [8,9,[55][56][57].…”
Section: Zebrafish Strains and Mutantsmentioning
confidence: 99%
“…Further studies have revealed that ift57 mutants form short outer segments but fail to maintain them, leading to rapid photoreceptor degeneration [ 110 , 111 ]. Both ift74 morphants and ift74 mutants exhibit outer segment degeneration [ 112 , 113 ]. Ift80 morphants fail to form outer segments, ultimately resulting in the apoptosis of photoreceptors [ 114 ].…”
Section: Cilia and Organogenesis In Zebrafishmentioning
confidence: 99%